The Microsoft case: what can a dominant firm do to defend its market position? - Klein, Benjamin (Journal of Economic Perspectives)
A case study describes Microsoft Corp.'s efforts to increase the use of its Internet Explorer technology—both by end users and software developers—in order to illustrate the strategies that a dominant firm may utilize. In this case, Microsoft is attempting to defend its market position in an effort to nullify the threat of Netscape Communications Corp. to Windows's dominance of the market for personal computer operating systems.